The determinants of corporate cash holdings levels: evidence from selected South African retail firms - Trust Chireka; Michael Bamidele Fakoya (Investment Management & Financial Innovations, 2017)
With corporate cash holdings on the rise, stakeholders need to know, among other things, what informs the companies’ cash holding policies and whether there are any benefits to be derived from piling up these cash reserves. Studies conducted in developed countries have identified the following as determinants of corporate cash holdings: firm size, growth opportunities, liquid asset substitutes, capital expenditure, leverage, dividend payments, cash flows and cash flow volatility. Few studies have focused on what drives firms’ cash holdings behavior in emerging economies. This study, the first of its kind, investigated the determinants of corporate cash holdings in the South African retail industry. The paper used panel data analysis to test the relationships between cash holdings level and the identified determinant factors. The authors found evidence that liquid asset substitutes, capital expenditure, dividend payments and cash flow volatility significantly influence the cash holdings levels of retail firms listed on the Johannesburg Stock Exchange.